PENGARUH UKURAN KAP, FINANCIAL DISTRESS, DAN AUDITOR SWITCHING TERHADAP AUDIT REPORT LAG - Arthur Jehezkiel; Siagian, Harlyn L. (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2022)
An auditor has an important role in a company, and an auditor also wants to have a good reputation in the eyes of his clients. One factors which can damage the reputation of an auditor is audit report lag, which is the time the audit work is completed until the time the audit report is issued. A long audit report lag can cause an auditor's reputation to be bad. Companies that have go public must also consider the length of the audit report lag time because it can affect the company's image in the public eye. Therefore, it is necessary to research the factors that affect the audit report lag. The population taken in this study is from the textile & garment and automotive & component sub-sector companies listed on the IDX in the 2017-2020 period. From this study’s results, it can be shown that financial distress affects audit report lag positively and significantly, while the variable size of KAP and auditor switching does not affect audit report lag.